2020
DOI: 10.1126/sciadv.abc2385
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene signaling mediates host invasion by parasitic plants

Abstract: Parasitic plants form a specialized organ, a haustorium, to invade host tissues and acquire water and nutrients. To understand the molecular mechanism of haustorium development, we performed a forward genetics screening to isolate mutants exhibiting haustorial defects in the model parasitic plant Phtheirospermum japonicum. We isolated two mutants that show prolonged and sometimes aberrant meristematic activity in the haustorium apex, resulting in severe defects on host invasion. Whole-genome sequencing reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…As pathogenicity and genetic diversity in the parasitic weed population are less well understood, understanding plant–plant interactions at the molecular level should go hand in hand with assessments of the genetic diversity of parasite populations. The recent availability of genomic information for S. asiatica (Yoshida et al ., 2019) and P. japonicum (Cui et al ., 2020), as well as transcriptome information on other Orobanchaceae plants (Yoshida et al ., 2010; Wickett et al ., 2011; Yang et al ., 2015; Kado & Innan, 2018; Lopez et al ., 2019), will allow comparative and ecological analyses that should deepen our understanding. The challenge now is to translate the information obtained from these resources into testable predictions about how parasites evade host immunity systems and to develop novel resistance strategies against parasitic weeds by identifying the molecular details of host immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As pathogenicity and genetic diversity in the parasitic weed population are less well understood, understanding plant–plant interactions at the molecular level should go hand in hand with assessments of the genetic diversity of parasite populations. The recent availability of genomic information for S. asiatica (Yoshida et al ., 2019) and P. japonicum (Cui et al ., 2020), as well as transcriptome information on other Orobanchaceae plants (Yoshida et al ., 2010; Wickett et al ., 2011; Yang et al ., 2015; Kado & Innan, 2018; Lopez et al ., 2019), will allow comparative and ecological analyses that should deepen our understanding. The challenge now is to translate the information obtained from these resources into testable predictions about how parasites evade host immunity systems and to develop novel resistance strategies against parasitic weeds by identifying the molecular details of host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has revealed that ethylene signaling is involved in the induction of intrusive cells. Two mutant lines in P. japonicum were identified that are defective in host invasion, and the phenotype was caused by mutations in key components of the ethylene signaling pathway, ETHYLENE RESPONSE 1 (ETR1) and a signaling transducer ETHYLENE INSENSITIVE 2 (EIN2) (Cui et al ., 2020). The mutants exhibit high cell proliferation activity at the haustorial apex and fail to differentiate intrusive cells even when touching host tissues.…”
Section: Host Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adapter and low-quality sequences were removed using the fastp software with default parameters (Chen et al, 2018). The quality-filtered reads were mapped to both the Phtheirospermum (Cui et al, 2020) and Arabidopsis genome (TAIR10) using STAR (Dobin et al, 2013) and were separated based on mapping to Phtheirospermum and Arabidopsis reads. The separated reads were then re-mapped to their respective genomes.…”
Section: Methodsmentioning
confidence: 99%
“…The gene expression clustering was performed using the Mfuzz software (Futschik et al, 2009). Custom annotations of the Phtheirospermum predicted proteins (Cui et al, 2020) were estimated using InterProScan (Blum et al, 2020), these were used for Gene ontology analysis that was performed using the topGO software (Alexa et al, 2016). ABA responsive, SA and cytokinin related genes in Phtheirospermum (TableS10) were identified using the tBLASTp and tBLASTp algorithm of the Arabidopsis ABA responsive genes described by (Nemhauser et al, 2006) or Arabidopsis genes involved in SA and CK pathways against the Phtheirospermum genome (Cui et al, 2020).…”
Section: Bioinformatic Analysismentioning
confidence: 99%